The Very Old in Randomized Surgical Intracerebral Hemorrhage Trails. Limitations Induced by Upper Age Limits. - Stein, Marco; Steiner, Thorsten; Misselwitz, Björn; Uhl, Eberhard.; H.T. Reinges, Marcus (Journal of Neurological Research And Therapy, 2016)
Spontaneous intracerebral hemorrhage (ICH) is one of the leading causes of death worldwide. In randomized trials on surgical therapy inclusion of the very old was limited by the recruitment process. This study was performed to evaluate the age limits in published surgical trials on ICH, and to determine how upper age limits effect the inclusion of men and women in these and future trials on the basis of a large cohort of ICH patients in central Europe. The Hessian stroke registry, a state-wide prospective stroke databank, was used to analyze upper age limits and sex differences for patients with the diagnosis of ICH (ICD-10: I61.0 to I61.9) who were admitted between January 2010 and December 2012. Sex differences were calculated at different age cutoffs, and the proportions of potentially excluded sex-specific patients from surgical trials on ICH were calculated. Overall, 5184 patients with the diagnosis of spontaneous ICH were identified. A total of 2457 (47.4%) patients were female and 2727 (52.6%) patients were male. Mean age was 72.3 ± 13.6 years. Female patients were significantly older compared to male patients (74.9 ± 13.5 years vs. 69.9 ± 13.2 years; p<0.001). With an upper age limit of 70, 75, and 80 years, 3437 patients (66.3%), 2664 patients (51.4%), and 1765 patients (34.0%) were excluded, respectively. Upper age limits in surgical trials on ICH could lead to the exclusion of a significant portion of patients from studies. This should be noted when transferring conclusions from these trials into clinical practice.
Keywords: intracerebral hemorrhage; age; very old; limitations; randomized trials